STRATEGI SUMBER DAYA MANUSIA DI ERA DIGITAL: MEMANFAATKAN MEDIA KOMUNIKASI PROFESIONAL UNTUK MENINGKATKAN KINERJA KARYAWAN - Tri Hemalia Ayu; Jhon Very (PT. Hasba Edukasi Mandiri, 2025)
The background of digital disruption demands a transformation in Human Resource Management (HRM) strategy. Professional communication media such as LinkedIn, Slack, and Microsoft Teams offer strategic opportunities that have not been fully optimized. This study aims to analyze and formulate a strategic HRM framework by leveraging professional communication media to enhance employee performance and engagement. The method used is a systematic literature review, analyzing credible sources from 2015 to 2024. The results identify three strategic areas for integrating these media: (1) Recruitment and Employer Branding via LinkedIn to attract passive talent and build an employer image; (2) Internal Communication and Collaboration via platforms like Microsoft Teams to break down silos and increase transparency; and (3) Employee Development through accessible microlearning and training. It is concluded that professional communication media is a critical component of modern HRM, whose effectiveness depends on leadership, organizational culture, and adequate training. The implication of this research encourages organizations to strategically integrate these platforms into HRM policies.